La coscienza situata come “polo opposto” della norma morale - Rajčáni, Jakub (Alpha omega, 2019)
In this paper, I examine the thought of Romano Guardini regarding human conscience and its consequences for moral theory. One specific feature of Guardini’s view of conscience is his focus on the concept of “situation”, which could make him appear close to the position of so-called “situation ethics”. However, situation is only one pole of reality, i.e., the subjective one, which as such requires another, objective pole – the norm. To explain this kind of relation I find the Guardinian image of “ellipse” particularly useful. Conscience cannot but be always located between the two foci of an existential ellipse: one’s own situation which requires certain action and the objective goodness of acts revealed in universal norms.